Morphological and Propagation Studies in some Chiuri types of Nepal - Shrestha, Sudhir; Chikanbanjar, Roshan; Bhandari, Nirajan; Pun, Umed Kumar (Nepalese Horticulture, 2024)
Diploknema butyracea (Chiuri) is a multi-use, under-utilized but economically and environmentally important native fruit tree species of Nepal. Earlier, four types of Chiuri were reported in Makwanpur district but recently about eight types has been reported from across the country. The main objective of the research was to study the morphology and propagation of six different types of Chiuri in Nepal. Leaves of six types of one year old grafted Chiuri was assessed, and vegetative propagation was tested in three types of Chiuri with side grafting and cleft grafting and during February, May, July, August and September 2021. Morphology of leaves showed differences in the pattern of leaves suggesting difference among them. Cleft grafting (47.7%) was found more effective than side grafting (41.7%) and early/mid-types were more responsive to grafting in contrast to late type. The best time for grafting early type of Chiuri was mid-July and not effective after August and before the month of May. Days to bud brust and first leaf opening was found earlier in cleft graft than side graft. Besides, the number of leaf was also higher in cleft graft in contrast to side graft suggesting better graft union in cleft graft than side graft. This research was focused on studying the morphology of the six types of Chiuri from four districts (Makwanpur, Chitwan, Rolpa and Dhading) and develop appropriate propagation technique for three different types of Chiuri collected from three districts (Makwanpur, Chitwan and Dhading).